PENGARUH PELATIHAN SERVICE EXCELLENT DAN EMPLOYEE ENGAGEMENT TERHADAP PENINGKATAN KINERJA KARYAWAN PADA BRI JEMBER (Studi Kasus BRI Unit Gajah Mada dan Unit Ajung) - Darmawan, Misbahul; Setyowati, Trias; Winahyu, Pawestri (Relawan Jurnal Indonesia, 2022)
In a very rapid business development like today, there are many banks, both conventional and non-conventional, making competition in the banking world very tight. To be able to survive and compete, banks must be able to develop various resources they have, one of the resources that must be developed is human resources or employees. Of course, every company wants to improve its performance, this increase can be achieved by one of the ways if employee performance also increases because employee performance is very sustainable with improving the performance of banking companies and is the spearhead who interacts directly with customers. However, increasing employee performance will not come by itself, several factors are needed to improve it, one way is by providing service excellent training (excellent service) because service can be one of the main elements of a company's success to win the competition and can make customers more loyal. Not only training can improve employee performance, there is another important factor, namely employee engagement because employees who still don't feel comfortable in the work environment, cannot work together with co-workers, and employees who feel unappreciated with their work will make the performance of employees worse. decreased, therefore the company must make employees feel engaged or feel belonging and valuable to be in the company it can make the performance of employees increase. One company that must improve the performance of its employees is BRI Jember (Gajah Mada Unit and Ajung Unit). The purpose of this study was to determine and analyze the effect of service excellent training and employee engagement on improving employee performance at BRI Jember (Gajah Mada Unit and Ajung Unit). This type of research is quantitative research using interview and questionnaire methods. The population in this study were employees of BRI Jember (Gajah Mada Unit and Ajung Unit). The sample used was 31 respondents using saturated sampling technique. The analysis tool uses multiple linear regression. The results of this study prove that service excellent training and employee engagement have a positive and significant impact on improving employee performance at BRI Jember (Gajah Mada Unit and Ajung Unit).